2015
DOI: 10.1038/srep17606
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of relative magnitudes of soil energy channels and their relationships with environmental factors in different ecosystems in Romania

Abstract: The percentage compositions of soil herbivorous, bacterivorous and fungivorous nematodes in forests, grasslands and scrubs in Romania was analysed. Percentages of nematode abundance, biomass and metabolic footprint methods were used to evaluate the patterns and relative size of herbivory, bacterial- and fungal-mediated channels in organic and mineral soil horizons. Patterns and magnitudes of herbivore, bacterivore and fungivore energy pathways differed for a given ecosystem type and soil depth according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Time has been found as positive factor for nutrient and trophic links recovery (Renčo et al, 2015). The order of values of nematode metabolic footprints was bacterivores > fungivores > herbivores that revealed bacterial-based energy channel in High Tatra spruce forest confi rmed results and conclusions of Ciobanu et al (2015) from analyses of soil samples collected in the Romanian coniferous forests.…”
Section: Discussionsupporting
confidence: 69%
“…Time has been found as positive factor for nutrient and trophic links recovery (Renčo et al, 2015). The order of values of nematode metabolic footprints was bacterivores > fungivores > herbivores that revealed bacterial-based energy channel in High Tatra spruce forest confi rmed results and conclusions of Ciobanu et al (2015) from analyses of soil samples collected in the Romanian coniferous forests.…”
Section: Discussionsupporting
confidence: 69%
“…In comparison with NPKS, greater values of structure index within >1 mm aggregates in CK indicated that the soil food web was a relatively complex community with few disturbances within larger aggregates 34 . Nematode metabolic footprints provide information on the responses of nematode assemblages to resources but are also an indication of the functions and services offered by nematodes 35 . In the present study, both manure application and straw incorporation increased soil nematode functional metabolic footprints within all aggregates ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A key component of soil biological health is the diversity of soil biota species within function classes performing these ecosystem services. The rates and magnitudes of these ecosystem services are determined by the composition and abundance of the diverse soil biota [5,6]. The assemblages of soil biota found in agricultural soils are known to be sensitive to management practices such as tillage, organic and inorganic amendments, pesticides and herbicides application and can be influenced by crop rotation since soil biota assemblages can be crop-specific [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%